Wannakhadi Phutthasatsana - Likhit Likhitanon; Mahawitthayalai Chiang Mai. Phak Wicha Phasa Thai. ([Chiang Mai, Thailand] : Phak Wicha Phasa Thai, Khana Manutsayasat, Mahawitthayalai Chiang Mai, 1987)
Study on Buddhist literature.
In Thai.
Includes bibliographical references (p. [135]-137).
Keywords: Buddhist literature -- History and criticism